An endogene-resembling transgene is resistant to DNA methylation and systemic silencing - Dadami, Elena; Wassenegger, Michael (RNA biology, 2014)
In plants, endogenes are less prone to RNA silencing than transgenes. While both can be efficiently targeted by small RNAs for post-transcriptional gene silencing (PTGS), generally only transgene PTGS is accompanied by transitivity, RNA-directed DNA methylation (RdDM) and systemic silencing. In order to investigate whether a transgene could mimick an endogene and thus be less susceptible to RNA silencing, we generated an intron-containing, endogene-resembling GREEN FLUORESCENT PROTEIN (GFP) transgene (GFPendo). Upon agroinfiltration of a hairpin GFP (hpF) construct, transgenic Nicotiana benthamiana plants harboring GFPendo (Nb-GFPendo) were susceptible to local PTGS. Yet, in the local area, PTGS was not accompanied by RdDM of the GFPendo coding region. Importantly, hpF-agroinfiltrated Nb-GFPendo plants were resistant to systemic silencing. For reasons of comparison, transgenic N. benthamiana plants (Nb-GFPcDNA) carrying a GFP cDNA transgene (GFPcDNA) were included in the analysis. HpF-agroinfiltrated Nb-GFPcDNA plants exhibited local PTGS and RdDM. In addition, systemic silencing was established in Nb-GFPcDNA plants. In agreement with previous reports using grafted scions, in systemically silenced tissue, siRNAs mapping to the 3′ of GFP were predominantly detectable by Northern blot analysis. Yet, in contrast to other reports, in systemically silenced leaves, PTGS was also accompanied by dense RdDM comprising the entire GFPcDNA coding region. Overall, our analysis indicated that cDNA transgenes are prone to systemic PTGS and RdDM, while endogene-resembling ones are resistant to RNA silencing.
Gesehen am 07.08.2020